Tezepelumab as add‐on treatment for severe asthma. Issue 3 (13th March 2023) - Chaplin, Steve
Abstract : Tezepelumab (Tezspire) is a new monoclonal antibody therapy for add‐on treatment in adolescents and adults with inadequately controlled severe asthma. This article outlines its mode of action, indication and clinical trial outcomes.